2022
DOI: 10.3390/ijerph191710688
|View full text |Cite
|
Sign up to set email alerts
|

The Most Common Handball Injuries: A Systematic Review

Abstract: Handball is a team sport involving a great physical demand from its practitioners in which a high number of injuries occur, affecting individual and collective performance. Knowledge of the injuries is of great importance for their prevention. The objective of the present study was to identify, locate and compare the most frequent injuries and injury mechanisms in handball practice. It was carried out following the Preferred Informed Item for Systematic Reviews and Meta-analysis (PRISMA) guidelines. The source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…The low incidence of 4.5 injuries per 1,000 match hours in our study may be related to the rather young age (15.7 ± 1.7 years) of this adolescent cohort. A lower injury incidence in this young age group is in line with different studies ( 3 , 4 ) and a review by Vila et al ( 9 ) that also reported fewer injuries in younger players. Importantly, no conclusions in terms of causation can be drawn from the present results.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The low incidence of 4.5 injuries per 1,000 match hours in our study may be related to the rather young age (15.7 ± 1.7 years) of this adolescent cohort. A lower injury incidence in this young age group is in line with different studies ( 3 , 4 ) and a review by Vila et al ( 9 ) that also reported fewer injuries in younger players. Importantly, no conclusions in terms of causation can be drawn from the present results.…”
Section: Discussionsupporting
confidence: 88%
“…This is especially true as the subjects have full control over their bodies with no perturbations during the YBT-UQ, while during training and games, balance is often challenged by body contact. It is well documented that body contact actions are an essential cause of injuries in handball ( 9 ) due to exposure to external forces ( 5 ). In addition, based on the notion that injuries are multicausal ( 40 ) and due to the possible interaction of many factors ( 38 ), weaknesses in one system (e.g., upper extremity mobility and stability as assessed by the YBT-UQ) may be compensated for by other systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Caine & Nassar, 2005;Ricard et al, 2007;Argibay-González et al, 2022), and the damages are mostly soft tissue (meniscal and ligamentous lesions). In combat sports, swimming, and volleyball, the shoulder joint suffers often (Wanivenhaus et al, 2012;Seminati & Minetti, 2013;Didace et al, 2017;Jeong et al, 2022), and in aesthetic sports, running, basketball, and handball -the ankle joint (McKay et al, 2001;Dagorov, 2002;Gamboa et al, 2008;Vila et al, 2022). D. Shoylev (1983) pays special attention to overuse injuries in various sports, e.g., ARS is mainly an overuse disease in soccer players, gymnasts, and wrestlers the shoulder joint is most affected; the knee joint -in weightlifters, volleyball players, and basketball players.…”
Section: Introductionmentioning
confidence: 99%